Pengaruh Terapi Kompres Hangat Terhadap Penurunan Nyeri Punggung Bawah pada Ibu Hamil - Anggraini Dyah Setiyarini; Erna Rahmawati (Journal of Pharmaceutical and Health Research, 2023)
Lower back pain in pregnant women is caused by hormonal changes. This causes changes in the supporting and connecting soft tissue. Result in decreased elasticity and flexibility muscle. One of the non-pharmacological therapies is warm water therapy. The benefits of a warm compress include increasing blood flow to areas of the body so that it can increase the flow of nutrients and relax muscles. The purpose of this study was to determine the effect of warm compresses on reducing low back pain in pregnant women at midwife Sri Wahyuni ​​Blitar. The research design used was Pre-Experimental. And the research design used is one group pre test-post test design. Sampling was carried out by means of non-probability sampling. The research sample consisted of 10 respondents who were selected using the Accidental Sampling technique. Collecting data with an observation sheet, using the NSR pain scale (Numeric Rating Scale). Data were analyzed using the Wilcoxon test to determine the effect of warm compresses on reducing low back pain. The Wilcoxon test results show a ρ value = 0.004, then <α (α = 0.05) then H₀ is rejected and H1 is accepted with an average difference between pretest and posttest which is 6.40 ± 4.50 so there is a decrease of 1.9 %. The conclusion from this study is that there is an effect of warm compresses on reducing pain in pregnant women. This study shows that warm water therapy can reduce lower back pain in pregnant women. It is hoped that warm compresses can be used as complementary therapy in pregnant women to reduce pain and can be combined with other therapies.